SERVICE-APPLIED MARTIAL ARTS IN THE PROFESSIONAL IMPROVEMENT OF EMPLOYEES OF INTERNAL AFFAIRS BODIES (World Bulletin of Social Sciences, 2023)
Physical training in the internal affairs bodies of the Republic of Uzbekistan is an integral part of the system of departmental vocational education, inextricably linked with the processes taking place in the sociopolitical and socio-economic life of the state. Fundamental changes in the basic characteristics of modern society, the increasing volume and complexity of tasks solved by the internal affairs bodies, changes in the qualitative parameters of crime cause the need for a high level of physical readiness of employees for effective law enforcement.
Keywords: physical fitness; employees of internal affairs bodies